Analisis Tingkat Kejenuhan Belajar Dan Kecemasan Belajar Peserta Didik Pada Masa Pandemi Covid 19 Dalam Mata Pelajaran Pendidikan Jasmani, Olahraga Dan Kesehatan Kelas Xi Di Smk Muhammadiyah 1 Padang - Yusrina Tambunan; Syahrastani Syahrastani; Gusril Gusril; Damrah damrah (JURNAL STAMINA, 2022)
The case in this research is about the chage of method in sport and health subject study in Pandemic, the education process should in practice in the field as almost with the own teacher’s control, and become almost material explanation dominantly about and add some task that makes boring an worrying to the students in studying. The research is made to see the rank of the student’s boring and worrying studying in pademic time for sport and health education subject in SMK Muhammadiyah 1 Padang. This research use quantitative-qualitative approachment (mixed methods) in sequential explanatory. The research population is Vocational High School (SMK) Muhammadiyah 1 Padang. At the beginning, the quantitative data is used here to collect the data, and then it uses qualitative. The tool for collecting data are questionair, interview, and document analyse. According to the result of stdent’s boring and worrying studying at the pandemi time on sport and health subject study, we can see that the level of the student’s boring feeling is the middle rank, by percentage 45,8%, and the worrying is also in the middle 45,8%.